Divergence and conservation of satellite DNA in the loggerhead sea turtle (Caretta caretta): a comparative cytogenomic analysis - Katerina V. Tishakova; Anastasia A. Proskuryakova; Dmitry Yu. Prokopov; Sergey A. Marchenko; Alessio Iannucci; Claudio Ciofi; Livia Tolve; Paolo Casale; Pasquale Salvemini; Natalia A. Serdyukova; Guzel I. Davletshina; Vladimir A. Trifonov; et al. (Chromosome Research, 2026)

Correction to: whole mitochondrial genome sequencing provides new insights into the phylogeography of loggerhead turtles (Caretta caretta) in the Mediterranean Sea - Livia Tolve; Alessio Iannucci; Luisa Garofalo; Andrea Ninni; Andrea Capobianco Dondona; Ilaria Ceciarini; Cristiano Cocumelli; Alessandra De Lucia; Mattia Falconi; Angela Formia; Federico Iacovelli; Cecilia Mancusi; et al. (Marine Biology, 2025)

Early detection of rare and elusive endangered species using environmental DNA: a case study for the Eurasian otter and the white-clawed crayfish in northwestern Italy - Lorenzo Ballini; Dario Ottonello; Valentina Repetto; Chiara Natali; Giacomo Chini; Livia Tolve; Claudio Ciofi; Sara Fratini; Alessio Iannucci (Conservation Genetics, 2024)
Monitoring, management and conservation of rare and elusive species often requires early detection of individuals, especially for re-introduced and endangered taxa. Environmental DNA (eDNA) approaches can enhance the detection power of traditional biomonitoring methods for low-density, newly-established populations. In this study, we used species-specific Real Time PCR TaqMan assays to assess the presence of two endangered freshwater species, the white-clawed crayfish Austropotamobius pallipes and the Eurasian otter Lutra lutra at eight sites in four river catchments in Liguria (northwestern Italy). The Eurasian otter was considered extinct in the study area since the 1980s. However, recent, although scattered sightings indicated a recolonisation by a few individuals. The white-clawed crayfish populations declined drastically and became increasingly dispersed in the western part of Liguria. Our eDNA analysis confirmed the presence of both species in some of the selected rivers and detected Eurasian otter DNA where the species was not recorded through traditional monitoring methods. This study confirms eDNA-based monitoring approaches as valuable tools to assess the presence of rare and elusive species and help implement protection plans at a local scale.

Whole mitochondrial genome sequencing provides new insights into the phylogeography of loggerhead turtles (Caretta caretta) in the Mediterranean Sea - Livia Tolve; Alessio Iannucci; Luisa Garofalo; Andrea Ninni; Andrea Capobianco Dondona; Ilaria Ceciarini; Cristiano Cocumelli; Alessandra De Lucia; Mattia Falconi; Angela Formia; Federico Iacovelli; Cecilia Mancusi; et al. (Marine Biology, 2024)
Population structure and phylogeography of the loggerhead sea turtle ( Caretta caretta ) have so far been assessed mainly by mitochondrial DNA (mtDNA) single-gene sequencing studies. However, phylogenetic relationships amongst matrilines, genetic characterisation of rookeries and mixed-stock analyses have suffered from the limited resolution obtained by comparison of relatively short sequences such as from the mtDNA control region. Whole mitogenome sequencing can significantly improve population genetics, particularly in marine organisms showing female natal philopatry. Despite mitogenomics becoming increasingly common in biodiversity monitoring and conservation, only a few complete mitogenomes are available for C. caretta . In this study, we sequenced the complete mtDNA of 61 loggerhead turtles sampled between 2008 and 2021 along the Italian coastline and central Mediterranean Sea. We assigned complete mtDNA haplotypes to dead embryos and bycatch samples, and introduced a first nomenclature for loggerhead mitogenomes. Analysis of mtDNA diversity, Maximum Parsimony and Bayesian phylogenetic reconstruction allowed improved resolution of lineages with respect to studies reporting on partial mtDNA control region sequence comparisons, and we were able to further inform previous analyses on loggerhead ancestry based on control region haplogroups. Overall, whole mitogenome analysis has potential for considerable improvement of evolutionary history and phylogeographic investigations as well as mixed-stock surveys of loggerhead turtles.

A comprehensive mitochondrial DNA mixed-stock analysis clarifies the composition of loggerhead turtle aggregates in the Adriatic Sea - Livia Tolve; Paolo Casale; Angela Formia; Luisa Garofalo; Bojan Lazar; Chiara Natali; Andrea Novelletto; Carola Vallini; Elena Bužan; Guido Chelazzi; Stefania Gaspari; Caterina Fortuna; et al. (Marine Biology, 2018)